Músicas tradicionales en espacios académicos: la rueda de gaita como experiencia de aprendizaje. (2016)
Traditional Colombian music has gained space in music education programs. Today, educators are concerned with finding ways to take advantage of these traditions in academia. This article focuses on the music of gaitas and drums of the Colombian Caribbean. Through a review of bibliographical material, research articles, papers and fieldwork, the musical elements and the teaching-learning processes present in this tradition are studied to find ways to take advantage of them in the academy. The analysis of the data obtained and the application of these in a practical experience suggest that la rueda de gaita is an effective tool for integrating musical knowledge and practice.